Design, Synthesis and Antibacterial Evaluation of some new 3,5-Diphenylcyclohex-2-en-1-one Derivatives - El-Saghier, Ahmed M.; A. Abd Allah, Omyma; M. Kadry, Asmaa (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
The moiety of cyclohexene has been showed highly antibacterial activity. New compounds were synthesized from diphenylcyclohexenone via reaction with a variety of reagents to afford branched chain of 1,3-diphenylcyclohexene or fused heterocyclic systems including pyrazole, chromen and pyrrole derivatives. Cyclic ketoketene s,s-acetal can be prepared by reaction with CS2/MeI under PTC conditions which in turn used as starting material for the synthesis of pyrazolyl and benzothiszolyl derivatives. Most of new synthesized compounds were characterized by using spectral data and were screened for their antibacterial activity.